Kesediaan Membayar Pelanggan Rumah Tangga Untuk Pelayanan Aair Bersih dari PDAM di Kabupaten Badung - Saraswaty, Amrita Nugraheni (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
This study aims to analyze the customers willingness to pay for clean water service that provided by PDAM in Badung Regency and identify the factors that influence the customers wilingness to pay for water service as a responce to the water service from PDAM in Badung Regency. Using Logistic Regression Model, the study found that customers willingness to pay for clean water connections varies between one region and others. Meanwhile, the significant factors that affect customers willingness to pay for clean water service are number of family members, quantity and quality of water, total family income, and ownership of water source beside the connection taps. While not significant factor that affect customers willingness to pay is the level of education.
Keywords: willingness; household; clean water; service; PDAM